موقف الحافظ أبي بكر الإسماعيلي في مسائل الإيمان والكفر من خلال كتابه (اعتقاد أهل السنة) - سليمان, أ. م. د. عبدالفتاح حسين; علي, أيوب محمد (Sulaimani Journal for Humanities, 2023)
Abu Bakr Al-Ismaili agreed with the Sunnis in defining faith. He also emphasizes that faith consists of saying it, practicing it and believing in it. Faith increases with obedience and decreases with disobedience, and there is no disagreement about that among the Sunnis. If Islam and faith are mentioned together in the same text, then the meaning of Islam is apparent actions, and the meaning of faith is belief. If Islam comes in one text and faith is in another text, their meanings unite. Disbelief is the opposite of faith, and it is divided into major and minor disbelief, and each of them has different types. The one who commits major sins weakens his faith but isn’t expelled from the circle of Islam by committing the sins unless he deems it lawful.